Navigating tensions in qualitative research: methodology, geography, personality and beyond. Issue 5 (20th October 2018) - Whitley, Meredith A.; Massey, William V.
Abstract: Increasingly, qualitative researchers are merging methods, processes and principles from multiple methodologies in all stages of a research study. Naturally, this brings tensions into the research process, with concerns about the integration (and/or lack of attention) of distinct historical, epistemological and theoretical approaches. While there is an emerging discourse connected to these methodological tensions, this often overlooks other tensions that qualitative researchers must navigate as part of a dyad or larger team. This includes tensions related to geography, project evolution, funding, personality, work style and student recruitment, training and supervision. In this paper, we share our experiences collaborating as a dyad on a multi-year qualitative research project that has evolved significantly (and still is), with a merging of methods, processes and principles from multiple methodologies (e.g. grounded theory, narrative inquiry). This evolution also includes shifting authorship and leadership on grants, presentations, publications and student supervision. To complicate matters, we live in different time zones with distinct personalities and work styles, with varying levels of funding and student engagement. We chronicle our experiences in this dyad, exploring the causes/effects of the various tensions and outlining the strategies we have adopted to navigate these tensions (e.g. ongoing reflection, honest communication, humour, dual focus on processes and outcomes). To conclude, we discuss the implications of these challenges, tensions and strategies as they relate to methodological rigour. Our hope is to provide a resource for future generations of qualitative researchers and their supervisors/instructors as they navigate the murky waters of qualitative research dyads.